Mid-term response assessment in multiple myeloma using a texture analysis approach on dual energy-CT-derived bone marrow images — A proof of principle study. Issue 131 (October 2020) - Reinert, Christian Philipp; Krieg, Eva-Maria; Bösmüller, Hans; Horger, Marius
Highlights: Texture analysis on VNC bone marrow images can enable myeloma response assessment. Both hematologic parameters and textural features are indicative of complete response. Bone marrow attenuation and heterogeneity change in parallel with disease activity. Abstract: Purpose: To identify textural features on dual-energy CT (DECT)-generated virtual non calcium (VNC) bone marrow images in a small group of patients with multiple myeloma undergoing systemic treatment which could potentially help for mid-term response assessment. Methods: 44 patients (59.1 ± 11.2 yr.) with multiple myeloma who underwent unenhanced whole-body reduced-dose DECT before and after systemic therapy were evaluated. All patients had current hematologic laboratory tests including serum levels of immunoglobulins, albumin, and total proteins. Using DECT post-processing, bone marrow images of the axial skeleton were reconstructed. The vertebral bodies T10–L5 were segmented for quantification of 1st order (n = 18) and 2nd order Gray Level Co-occurrence Matrix (GLCM) textural features (n = 23) based on an open-source radiomics library (Pyradiomics), which were then compared with the hematologic response category to treatment. Five patients underwent only active surveillance at intervals after previous successful therapy. Results: According to hematologic diagnosis, 29 patients were classified as complete response (CR), 10 as partial response (PR) and 5 as stable disease (SD). We observed a significant drop of the 1st order textural features "10th percentile" (p = 0.009), "median" (p = 0.01), and "minimum" (p < 0.0001) after treatment, whereas the 1st order feature "range" (p = 0.0004) and the 2nd order GLCM feature "difference variance" (p = 0.007) significantly increased in patients experiencing CR. A similar trend, however, without statistical significance, could be observed in patients achieving PR after treatment. 2nd order GLCM feature "difference variance" proved to be a significant discriminator (p = 0.01) between patients with CR and PR (sensitivity 0.93, specificity 0.70) for a cut-off value of -0.28. In patients classified CR, both the mean serum protein and the beta-2 microglobulin decreased after treatment, whereas the serum albumin increased (p < 0.01). The same trend without significance could be observed in patients classified PR. Conclusions: Changes in textural features applied on VNC bone marrow images in the pre- and posttreatment settings correlate well with myeloma-specific hematologic parameters and provide complementary information for the assessment of the late effects of treatment on the bone marrow.